PRODUKTIVITAS DAN RENDEMEN PEMBUATAN PINTU DARI KAYU ULIN (Eusideroxylon zwager) DAN KAYU DURIAN (Durio zibethinus) DI PERUSAHAAN ULIN HIDAYAH, LANDASAN ULIN BANJARBARU KALIMANTAN SELATAN - Dwi Rita Sari; Kurdiansyah Kurdiansyah; Noor Mirad Sari (Jurnal Sylva Scienteae, 2026)
This research is entitled productivity and yield of door making from ulin wood and durian wood in the ulin hidayah company. This study aims to calculate the average productivity and yield of making doors from ulin wood (Eusideroxylon zwager) and durian wood (Durio zibethinus) at Ulin Hidayah Company. Productivity is a comparison of the effectiveness of producing outputs and inputs with the labor system (input). Yield is the ratio between input and output expressed in percent. The calculation of productivity uses a stopwatch with the zero stop method. Yield is calculated as a percentage and a comparison between input and output in percent. The productivity results of ulin wood door making produced an average of 0.039 m3/hour while durian wood produced an average of 0.036 m3/hour. The yield of ulin wood door making results in an average of 64.92%, while durian wood produces an average of 42.4%.